Performance evaluation of nonlinear viscoelastic materials using finite element method - Sabri, Laith Abed; Al-Tamimi, Adnan Naji Jameel; Alshamma, Fathi A.; Mohammed, M.N.; Salloomi, Kareem N.; Abdullah, Oday I. (Zielona Góra: Uniwersytet Zielonogórski)
This research paper applies the finite element method as a methodology to evaluate the structural performance of nonlinear viscoelastic solids. A finite element algorithm was built and developed to simulate the mathematical nonlinear viscoelastic material behavior based on incremental constitutive equations. The derived Equation of the incremental constitutive included the complete strain and stress histories.
Keywords: Finite Element Method (FEM); viscoelastic; nonlinear analysis; uniaxial and multiaxial stresses formulation